O processo de produção na animação brasileira contemporânea: um estudo sobre Uma história de amor e fúria - Eduardo dos Santos Oliveira (2022)
The present work aims to enable a reflection on the production process of animated feature films in Brazil, through the selection of the production stages of the Brazilian animated feature “Uma História de Amor e Fúria”, from 2013, written and directed by Luiz Bolognesi. In order, the research is based on bibliographic research, such as the dissertation by Antônio Fialho, from 2005, on the methodology of classic animation and, also, the third edition of the book Producing Animation (2020), by the authors Catherine Winder and Zahra Dowlatabadi, about the production process in animation. As a methodology, the documentary research was used, with the analysis of the film itself and material references to it (making of, interviews with the director or with members of the team). In addition to Bolognesi's feature film, seven other Brazilian films were chosen to have part of their processes studied. The films are from different periods and techniques, with the aim of following the evolution of Brazilian production over the decades. It was observed that, among other issues, the financial matter influences the production process of national animated films, as their budgets are smaller compared to large foreign productions. Thus, they cannot incorporate the entire making process of these studios.